Scent-marking strategies of a solitary carnivore: boundary and road scent marking in the leopard. (March 2020) - Rafiq, Kasim; Jordan, Neil R.; Meloro, Carlo; Wilson, Alan M.; Hayward, Matthew W.; Wich, Serge A.; McNutt, John W.
Abstract : Scent marking, where individuals deposit signals on objects in the environment, is a common form of chemical signalling in mammals and is thought to play a critical role in maintaining social organization within wide-ranging, spatially dispersed populations. Senders, however, can incur scent-marking costs through mark production, time investment in patrolling and depositing/maintaining mark sites, and increased risk of detection by predators and prey. To mitigate these costs, senders can adapt spatial patterns of scent marking to increase the probabilities of their scent marks being encountered by intended receivers. Relatively little, however, is known of the spatial scent-marking placements of many wide-ranging carnivore species, with most studies focusing on scent mark form and function. Here, we used detailed observational data collected from over 7 years of following individual leopards, Panthera pardus, and high-resolution GPS radiocollar data to investigate the spatial placements of scent marks within a leopard population in northern Botswana. We found that male leopards within our study area had a boundary scent-marking strategy, investing more in maintaining marking sites in peripheral areas of their home range. We also found that leopards scent-marked over four times as frequently and investigated over three times as frequently when travelling on roads than when travelling along natural routes, suggesting that roads may function as key locations for olfactory information. Compared to leopards from less productive ecosystems, such as the Kalahari, our results (1) suggest that leopards can be highly flexible in their marking strategies, with strategies impacted by the surrounding environment, and (2) provide evidence that human modifications of the environment now play an important role in facilitating social cohesion within this solitary carnivore. Highlights: Species can use spatial scent-marking strategies to facilitate communication. Leopards showed higher investment in maintaining scent marks at home range boundaries. Communication behaviours are impacted by human modifications to the environment. Leopards are highly flexible in their scent-marking strategies. GPS and focal data can provide greater insights into cryptic species' behaviours.